Analysis of Optimal Stock Portfolio Formation Using the Single Index Model as the Basis for Investment Decisions - Hermin Sirait; Wanda Nur Hanifah; Devi Anggraeni; Shenda Aprilia Christanti (Green Publisher Indonesia, 2024)
Calculation and determination the optimal portfolio by Single Index Model method, which involves several stages of calculation. These stages comprise the determination of the optimal portfolio and the identification of the optimal proportion of funds to be invested in the securities that included in the optimal portfolio. This study also presents the results of the return and risk analysis of the optimal portfolio securities. A sample of LQ45 listed, and seven optimal portfolio stocks were identified are Barito Pacific Tbk (BRTP), Medco Energi Internasional Tbk (MEDC), Indofood Sukses Makmur Tbk (INKP), Bank Mandiri (Persero) Tbk (BMRI), Mitra Pack Tbk (PTMP), Essa Industries Indonesia Tbk (ESSA), and GoTo Gojek Tokopedia Tbk (GOTO).